ChemInform Abstract: An Expedient Synthesis of Oxindole Dimers by Direct Oxidative Dimerization of Oxindoles. Issue 52 (24th December 2013) - Lee, Hyun Ju; Lee, Sangku; Lim, Jin Woo; Kim, Jae Nyoung
Abstract using manganese (III) acetate or copper acetate/silver acetate systems